Clinical laboratory evaluation of the automicrobic system Enterobacteriaceae biochemical card. - Davis, J R (1981)
The AutoMicrobic System Enterobacteriaceae Biochemical Card (AMS-EBC; Vitek Systems, Inc.) was evaluated in two clinical microbiology laboratories. A total of 502 consecutive clinical isolates representing members of the family Enterobacteriaceae were tested in parallel with the AMS-EBC, API 20E, and Enterotube II systems. Discrepancies between systems were resolved with the conventional methods of Edwards and Ewing (P. R. Edwards and W. H. Ewing [ed.], Identification of Enterobacteriaceae, 1972) and Ewing and Martin (W. H. Ewing and W. J. Martin, in Manual of Clinical Microbiology, 1974) AMS-EBC correctly identified 96.6% and incorrectly identified 3.4% of the isolates. When 12 or more isolates of a species were evaluated, Serratia marcescens, Proteus mirabilis, and Enterobacter cloacae posed the greatest challenge to the systems, with 92.6, 95.2, and 95.3%, respectively, being correctly identified. To confirm the accuracy of identification when all systems agreed, 93 randomly selected isolates were identified by conventional methods. The percent agreement was 100%. The reproducibility of triplicate determinations on 93 randomly selected isolates with the AMS-EBC was 99.6%. The AMS-EBC was found to be an easy, rapid, and accurate method for identification of Enterobacteriaceae.